Der deutsche NPL-Markt 2007: aktuelle Entwicklungen, Verkauf und Bewertung ; Berichte und Referate des NPL-Forums 2007 - Christoph Schalast (Frankfurt School of Finance & Management, 2008)
The work report first describes the current developments on the German market for nonperforming loans, which after its peak in spring 2007 is now also affected by the financial crisis. The sale of small and medium-size portfolios is described within the scope of a case study. Furthermore, the report focusses on the automated and trustworthy assessment and the servicing of real property portfolios.
urn:nbn:de:101:1-2008082944
Keywords: K12; K19; K22; K29; 330; Non performing loans; distressed debt; portfoliomanagement; workout; outsourcing; servicing; banking and regulation law; bankers duty of secrecy; failing banks; corporate loans; consumer loans; real estate loans